Replacing the projected retiring baby boomer nursing cohort 2001 - 2026 - Schofield Deborah J (BMC, 2007)
Abstract Background The nursing population in Australia is ageing. However, there is little information on the rate and timing of nursing retirement. Methods Specifically designed health workforce extracts from the Australian Bureau of Statistics (ABS) censuses from 1986 to 2001 are used to estimate the rate of nursing retirement. The 2001 nursing data are then "aged" and retirement of the nursing workforce projected through to 2026. ABS population projections are used to examine the future age structure of the population and the growth and age distribution of the pool of labour from which future nurses will be drawn. Results Attrition rates for nurses aged 45 and over are projected to be significantly higher between the base year of 2006 and 2026, than they were between 1986 and 2001 (p < 0.001). Between 2006 and 2026 the growth in the labour force aged 20 to 64 is projected to slow from 7.5 per cent every five years to about 2 per cent, and over half of that growth will be in the 50 to 64 year age group. Over this period Australia is projected to lose almost 60 per cent of the current nursing workforce to retirement, an average of 14 per cent of the nursing workforce every five years and a total of about 90,000 nurses. Conclusion The next 20 years will see a large number of nursing vacancies due to retirement, with ageing already impacting on the structure of the nursing workforce. Retirement income policies are likely to be a key driver in the retirement rate of nurses, with some recent changes in Australia having some potential to slow retirement of nurses before the age of 60 years. However, if current trends continue, Australia can expect to have substantially fewer nurses than it needs in 2026.